The structure and nanoindentation of C₆₀ films - Pukha, V.E.; Drozdov, A.N.; Pugachev, A.T.; Dub, S.N. (Functional Materials, 2007)
The epitaxial (111) oriented fullerite films have been prepared by condensation of C₆₀ molecules onto mica substates in a quasi-closed volume. The hardness H = 0.55±0.17 GPa and Young`s modulus E = 15±1 GPa of the fullerite films along the (111) direction of the film fcc lattice have been deterimined.